Advanced Two-Stage Nanocomposite Membrane System for Methane and Carbon Dioxide Separation from Atmospheric Air - SERROUNE, Shad Abdelmoumen; GEIOS, Nano; KAIGEN,; S.T., Dr. Ir. Khasani; SERROUNE, Hicham; LEE, Hyungson; SANGHO, Ryan Lee; KYU, Lee Dong; SOO, Lee Young (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper presents an advanced two-stage nanocomposite membrane system designed to efficiently separate and capture methane (CH4) and carbon dioxide (CO2) from atmospheric air and water sources. The membrane system comprises a CO2-selective primary membrane and a CH4-selective secondary membrane, utilizing a hierarchical nanomaterials and polymers structure. The proposed system demonstrates unprecedented versatility, operating effectively across an extensive range of gas concentrations (>20% to 50. Furthermore, experimental validation over 1000 hours of continuous operation demonstrated 92% methane capture efficiency under challenging conditions (55 tons/hour methane content at 30 °C). The system's energy consumption of 0.3 kWh/kg of CH4 captured underscores its efficiency compared to traditional methods. This innovative membrane technology offers a promising solution for addressing critical ecological and industrial challenges associated with greenhouse gas emissions in the 21st century.